The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2141/jpsa.0130154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with <i>Aspergillus Awamori </i>on Growth Performance and Antioxidative Status of Broiler Chickens Exposed to High Ambient Temperature

Abstract: This study was conducted to evaluate the effects of dietary supplementation with Aspergillus awamori on the growth performance and antioxidative status in male broiler chickens exposed to high ambient temperatures. Twentyfour 15-d-old male broiler chickens were randomly divided into 2 dietary groups fed a corn-soybean meal-based diet supplemented without or with 0.05% of Asp. awamori. Six birds of each dietary group were kept under a thermoneutral condition (22℃), and 6 birds were exposed to heat stress (35℃, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…These chicks were housed individually in wire‐bottomed aluminum cages (50 × 40 × 60 cm) and fed a basal diet (see Table for diet composition) for 3 days until beginning of the main experimental period. Heat exposure experiment was designed according to our previous studies (El‐Deep, Ijiri, Ebeid, & Ohtsuka, ; El‐Deep, Ijiri, Eid, Yamanaka, & Ohtsuka, ). Panaferd‐P supplementation (0.15%) was determined to adjust to the Astaxanthin concentration (30 ppm) of the previous study (Akiba, Sato, Takahashi, Matsushita, et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…These chicks were housed individually in wire‐bottomed aluminum cages (50 × 40 × 60 cm) and fed a basal diet (see Table for diet composition) for 3 days until beginning of the main experimental period. Heat exposure experiment was designed according to our previous studies (El‐Deep, Ijiri, Ebeid, & Ohtsuka, ; El‐Deep, Ijiri, Eid, Yamanaka, & Ohtsuka, ). Panaferd‐P supplementation (0.15%) was determined to adjust to the Astaxanthin concentration (30 ppm) of the previous study (Akiba, Sato, Takahashi, Matsushita, et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that A. awamori produces antioxidative substances. Indeed, an increase in TBARS levels in the breast muscle of broiler chickens induced by heat stress was negated by feeding a diet containing A. awamori (El-Deep et al, 2014). In addition, feeding diets containing A. awamori increased the mRNA expressions of antioxidant enzymes (i.e., glutathione peroxidase, catalase and superoxide dismutase).…”
mentioning
confidence: 99%
“…The result indicated that hyperglycemia induced by alloxan administration was ameliorated by feeding of only A. awamori. Several researchers reported that dietary intake of A. awamori improved an intestinal environment and induced increase of α-tocopherol (vitamin E) level in their blood and muscles to affect the lipid and protein metabolism (El-Deep et al, 2014;Saleh et al, 2013Saleh et al, , 2014. As the intake of vitamin E improved mouse hyperglycemia caused by alloxan and vitamin E improved insulin release from pancreas damaged by alloxan (Kamimura et al, 2013;Takemoto, Doi, & Masuoka, 2016), we deduced that A. awamori is an effective probiotic and increases vitamin E to ameliorate hyperglycemia induced by oxidative stress.…”
Section: Discussionmentioning
confidence: 84%